PENGGUNAAN MEDIA JOB SHEET SEBAGAI UPAYA PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS VII.1 DALAM PEMBELAJARAN KETERAMPILAN ANYAMAN DI SMPN 2 AMPEK NAGARI - NURNI, Drs. Yusron Wkarya,M.Pd, Drs. Muznin Ramanto (Serupa The Journal of Art Education, 2014)
This research is a classroom action research, the research was conducted inthe semester from January to June 2014 VII.1 grade SMP 2 Ampek Nagari the number 30 in the skill woven material. Classroom action research was carried out by 2 cycles with steps of research, namely, (1) planning (Planning), (2) the action (Action), (3) observation (Observation), (4) reflection (Reflection). This study uses the theory of UNO (2008: 16) were used as a reference in enhancing students' motivation and learning outcomes in the payment of the skills VII.1 grade webbing.From the research data obtained an increase in student belar visible results from the first cycle and the second cycle is as follows: First, the use of job media sheets can improve the motivation of students in learning the skills to make the fan woven from bamboo with an average student motivation in the first cycle of 6, 50 and the second silkus increased to 7.41. Secondly, the use of job sheet media can improve student learning outcomes of learning skills in making wicker fan of bamboo with an average of 60.73 for the first cycle and the second cycle increased to 81.17. The results of this study indicate that the use of job sheets can improve motivation and learning outcomes of students in learning skills webbing.Keywords: media, job sheet, motivation, learning, webbing.